The achievements and perspective trends of electrically welded anastomosis - S. S. Podpriatov; S. E. Podpryatov; G. S. Marynskyy; O. V. Chernets; V. A. Tkachenko; D. A. Grabovsky; K. G. Lopatkina; S. V. Tkachenko; Y. Z. Buryak; V. K. Serdyuk (Сучасні медичні технології)
In result of previous studies, we found the superior qualities of electro-welded intestinal anastomoses had created by using tools and models are suitable for open surgery.